Using a RESTful messaging and registry system to support a range a distributed applications - Baker, Mark; Mills, Hugo; Smith, Garry; Grove, Matthew; Lakhoo, Rahim; Albing, Carl (Revista Colombiana de Computación, 2010)
Tycho was conceived in 2003 in response to a need by the GridRM [1], a resourcemonitoring project for a “light-weight”, scalable and easy to use wide-area distributed registry and messaging system. Since Tycho's first release in 2006 a number of modifications have been made to the system to make it easier to use and more flexible. Since its inception, Tycho has been utilised across a number of application domains including wide-area resource monitoring, distributed queries across archival databases, providing services for the nodes of a Cray supercomputer, and as a system for transferring multi-terabyte scientific datasets across the Internet. This paper provides an overview of the initial Tycho system describes a number of applications that utilise Tycho, discusses a number of new utilities, and how the Tycho infrastructure has evolved in response to experience of building applications with it.